Determinants of climbing performance: When finger flexor strength and endurance count - Marcolin, G.; Faggian, S.; Muschietti, M.; Matteraglia, L.; Paoli, A. (The Journal of Strength and Conditioning Research, 2022)
Aim of the study was: (a) to compare finger flexor strength and endurance among climbers and nonclimbers; (b) to predict climbers' level of ability using climbing-specific strength tests and prolonged fatigue protocols. 17 advanced climbers (ADV), 17 intermediate climbers (INT), and 15 nonclimbers (NOCLIMB) performed a maximal finger grip test on a climbing-specific device, a maximal handgrip test, 20 intermittent isometric maximal contractions (E1), a suspension test on a bar till exhaustion, and again 20 intermittent isometric maximal contractions (E2). Strength values were normalized to body weight (%BW). The handgrip test failed to discriminate ADV from INT. Maximal finger flexor strength differed among ADV (59.90 ± 9.42 %BW), INT (46.75 ± 8.40 %BW) and NOCLIMB (36.40 ± 6.51 %BW) (p < 0.0001; ?2p: 0.586). ADV showed the best suspension time (58.55 ± 14.87 seconds) followed by INT (32.55 ± 16.87 seconds) and NOCLIMB (17.20 ± 14.30 seconds) (p < 0.0001; ?2p: 0.563). ADV showed the best endurance performance in both E1 and E2. The highest correlations with climbers' ability scores were obtained with sport-specific tests (maximal finger strength, r = 0.60, p < 0.0001; bar suspension, r = 0.69, p < 0.0001) and at the highest level of fatigue (E2, r = 0.74, p < 0.0001). Strength and endurance gain more importance in determining climbers' ability if assessed with finger specific tests and after prolonged fatigue.